Prospective randomized trial of interferon Alfa-2b and Interleukin-2 as adjuvant treatment for resected intermediate- and high-risk primary melanoma without clinically detectable node metastasis - Hauschild, Axel; Schadendorf, Dirk (Journal of clinical oncology, 2016)
Purpose: Low-dose interferon alfa (IFNα) has been shown to have limited effects in the adjuvant treatment of patients with intermediate- and high-risk primary melanoma. We hypothesized that a combination regimen with low-dose interleukin-2 (IL-2) may improve survival prospects in these patients. Patients and Methods: After wide excision of primary melanoma without clinically detectable lymph node metastasis (pT3 to 4, cN0, M0), 225 patients from 10 participating centers were randomly assigned to receive either subcutaneous low-dose IFNα2b (3 million international units [MU]/m2/d, days 1 to 7, week 1; three times weekly, weeks 3 to 6, repeated all 6 weeks) plus IL-2 (9 MU/m2/d, days 1 to 4, week 2 of each cycle) for 48 weeks, or observation alone. The primary end point was prolongation of a relapse-free interval. Results: Of the 225 enrolled patients, 223 were found to be eligible. Median follow-up time was 79 months. All evaluated prognostic factors were well balanced between the two arms of the study. Relapses were noticed in 36 of 113 patients treated with IFNα2b plus IL-2 and in 34 of 110 patients with observation alone. Five-year disease-free survival of those who had routine surgery supplemented by IFNα2b and IL-2 treatment was 70.1% (95% confidence interval [CI], 61.3% to 78.9%), compared with 69.9% in those receiving surgery and observation alone (95% CI, 60.7% to 79.1%) in the intention-to-treat analysis. Evaluation of the overall survival did not show any difference between treated and untreated melanoma patients (P = .93). Conclusion: Adjuvant treatment of intermediate- and high-risk melanoma patients with low-dose IFNα2b and IL-2 is safe and well tolerated by most patients, but it does not improve disease-free or overall survival.
Elektronische Reproduktion der Druckausgabe
Gesehen am 23.11.2020